RESEARCH OF STEADY CONDITIONS OF MODELS OF INTERACTION OF COMMUNITIES - Tatyana Konstantinovna Pritula; Anna Stanislavovna Adamchuk (Вестник Северо-Кавказского федерального университета)
Results of research of stability are given in article on the example of some special cases of model of Lotki – Volterra of interaction of two views with different managing directors in coefficients, and also model of a repro-duction of DNA for N types.